Genetic interaction between placental growth factor and vascular endothelial growth factor A in psoriasis. (30th October 2019) - Young, H. S.; Kamaly‐Asl, I. D.; Laws, P. M.; Pemberton, P.; Griffiths, C. E. M.
Summary: Background: Expression of vascular endothelial growth factor A (VEGFA) is increased in chronic inflammatory skin diseases, including psoriasis, and loci for two VEGFA single nucleotide polymorphisms are associated with early‐onset psoriasis (presenting before the age of 40 years). Studies have suggested that expression of placenta growth factor (PGF) is also upregulated in cutaneous inflammation and that VEGFA‐mediated angiogenesis may be dependent on the simultaneous presence of PGF within the skin. Aim: To elucidate the biological importance of PGF in psoriasis. Methods: We investigated whether two commonly occurring PGF polymorphisms were associated with early‐onset psoriasis and the genetic interaction between VEGFA and PGF in psoriasis. Results: We observed a significant ( P = 0.04) association between rs2268614 TT and rs2268615 AA genotypes of PGF and early‐onset psoriasis. In addition, genetic complement, comprising the PGF rs2268615 AA genotype and the VEGFA −460 (rs833061) T allele, was significantly associated with the development of early‐onset psoriasis ( P < 0.03). We identified that the VEGFA genotype influences PGF expression ( P = 0.001) and that mean plasma levels of PGF are lower in patients with severe psoriasis compared with those with mild–moderate disease ( P = 0.04). Conclusion: Our observed genetic interaction between PGF and VEGFA appears relevant to psoriasis, a disease with an angiogenic basis, and may influence development of an antiangiogenic approach to treatment.